2022
DOI: 10.1177/10935266221079569
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Pathologic Characteristics in Myhre Syndrome: Gain-of-Function Pathogenic Variants in SMAD4 cause a Multisystem Fibroproliferative Response

Abstract: Background: Myhre syndrome, caused by pathogenic variants in SMAD4, is characterized by compact body habitus with short stature, distinctive craniofacial appearance, stiff skin, cardiovascular abnormalities (valve stenosis, coarctation, hypoplasia, or stenosis of aorta), effusions of potential spaces (pericardium, pleura, peritoneum), restricted movement of the joints (including thorax), and hearing loss. Lung and airway disease has been reported, but not always well-defined, to include interstitial lung disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In a subsequent review of the pathologic features of Myhre syndrome, this woman was correctly reported (tab. 1, Patient 14 in Starr et al, 2022).The authors regret the error and acknowledge the clinical implications for correcting the SMAD4 variant in this paper. The original observation that all (three of three) of the reported women with endometrial cancer had the NM_005359.6(SMAD4):c.1486C>T (p.Arg496Cys) variant may have overstated the association.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In a subsequent review of the pathologic features of Myhre syndrome, this woman was correctly reported (tab. 1, Patient 14 in Starr et al, 2022).The authors regret the error and acknowledge the clinical implications for correcting the SMAD4 variant in this paper. The original observation that all (three of three) of the reported women with endometrial cancer had the NM_005359.6(SMAD4):c.1486C>T (p.Arg496Cys) variant may have overstated the association.…”
mentioning
confidence: 90%
“…In a subsequent review of the pathologic features of Myhre syndrome, this woman was correctly reported (tab. 1, Patient 14 in Starr et al, 2022).…”
mentioning
confidence: 99%